Perlindungan Hukum Terhadap Pembeli Beritikad Baik dalam Sengketa Tanah: Tinjauan Yuridis Perdata dan Praktek Peradilan di Pengadilan Denpasar - Lumban Tobing, Daniel Reynaldi Lumban Tobing; Urbanisasi, Urbanisasi (Zaaken: Journal of Civil and Business Law, 2026)
This study aims to analyze the form of legal protection for good faith buyers in the Indonesian civil law system, focusing on the case study of the Mulia Bali Hotel. Legal problems arise when buyers who have made transactions legally and fulfill the elements of good faith still experience legal losses due to third party lawsuits or legal defects in the object of the transaction. The method used is a normative legal approach and case studies, with an analysis of court decisions and relevant national civil regulations. The results of the study indicate that the Indonesian civil law system has not provided maximum guarantees for good faith buyers, especially in disputes over ownership of immovable objects. Therefore, it is necessary to reformulate norms and strengthen the principle of justice in legal protection for good faith buyers.